How recycling and transformation information influences tourists’ purchase intentions towards green food products - Liangyu Wang; Dajun Yang (CyTA - Journal of Food, 2025)
This study aims to provide an in-depth analysis of the influence and mechanisms of recycling and transformation information on product packaging towards tourists’ purchasing intentions. Through four experiments, we found that product packaging featuring recycling and transformation information significantly enhanced tourists’ purchase intentions, and this effect was partially mediated by tourists’ Information seeking behavior. Notably, in the context of organic food packaging, tourists with a high level of environmental concern exhibited a more positive response to recycling and transformation information. Additionally, the study revealed that a positive environmental attitude strengthened the positive impact of recycling and transformation information on purchasing intentions. These findings not only enrich theoretical knowledge in the field of green consumption but also offer valuable practical guidance for businesses and governments in promoting environmentally friendly consumption practices.